Kinerja Program Mustahik Pengusaha BAZNAS: Kajian Indeks Pendayagunaan Zakat - Azzahra, Shifa Fadillah; Munawar, Wildan (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
AbstractThis research aims to determine the performance of the Mustahik Entrepreneur program by studying the Zakat Utilization Index, so that it can be used as evaluation material for BAZNAS in decision making. his research is a descriptive quantitative method with data collection methods through questionnaires and interviews. The method used in this research is using the Zakat Utilization Index with a calculation called the Multi-Stage Weighted Index. The research results show that the performance of the Mustahik Entrepreneur program produces a Zakat Utilization Index (IPZ) value of 0.60 in the quite good category and is in the strengthening phase, where the empowerment program implemented is starting to run according to target and has had quite a good impact. The da'wah indicator was ranked first at 0.69, the social indicator at 0.63, the economic indicator at 0.59, the environmental indicator at 0.58. Lastly isthe cultural indicator which received a less favorable interpretation of 0.45. This program has had quite a good impact on mustahik as a whole, where it also motivates members to try to carry out social activities and do charity, fosters the development of mustahik entrepreneurial culture through group discussions, provides material and nonmaterial additions to mustahik, helps motivate mustahik to enter into entrepreneurship in a halal and good manner as well as the existence of mustahik awareness of protecting the surrounding environment.Keywords: Entrepreneur Mustahik Program; Zakat; Zakat Utilization; Zakat Utilization IndexAbstrakPenelitian ini bertujuan untuk mengetahui kinerja program Mustahik Pengusaha dengan kajian Indeks Pendayagunaan Zakat, sehingga dapat dijadikan sebagai bahan evaluasi bagi BAZNAS dalam pengambilan keputusan. Penelitian ini menggunakan metode kuantitatif deskriptif dengan metode pengumpulan data melalui kuesioner dan wawancara. Pendekatanmenggunakan Indeks Pendayagunaan Zakat dengan penghitungan yang disebut Multi-Stage Weighted Index. Hasil penelitian menunjukan kinerja program Mustahik Pengusaha menghasilkan nilai Indeks Pendayagunaan Zakat (IPZ) sebesar 0,60 dengan kategori cukup baik dan berada pada fase penguatan, dimana program pemberdayaan yang dijalankan mulai berjalan sesuai sasaran dan telah memberikan dampak cukup baik. Indikator dakwah menempati peringkat pertama sebesar 0.69, indikator sosial sebesar 0.63, indikator ekonomi sebesar 0.59, indikator lingkungan sebesar 0.58. Terakhir adalah indikator budaya yang memperoleh interpretasi kurang baik sebesar 0.45. Program ini memberikan dampak cukup baik bagi mustahik secara keseluruhan, dimana turut memotivasi antar anggota untuk berusaha melakukan kegiatan sosial maupun beramal, menumbuhkan pengembangan budaya kewirausahaan mustahik melalui diskusi kelompok, adanya pertambahan material maupunnon material pada mustahik, turut memotivasi mustahik berwirausaha secara halal dan baik serta adanya kesadaran mustahik pada menjaga lingkungan sekitar.Kata kunci: Indeks Pendayagunaan Zakat (IPZ); Pendayagunaan Zakat; Program Mustahik Pengusaha ; Zakat